2018
DOI: 10.1021/acs.accounts.8b00519
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evolution of Mechanistic Understanding in Iron-Catalyzed Cross-Coupling

Abstract: Since the pioneering work of Kochi in the 1970s, iron has attracted great interest for crosscoupling catalysis due to its low cost and toxicity as well as its potential for novel reactivity compared to analogous reactions with precious metals like palladium. Today there are numerous iron-based cross-coupling methodologies available, including challenging alkyl-alkyl and enantioselective methods. Furthermore, cross-couplings with simple ferric salts and additives like NMP and TMEDA (N-methylpyrrolidone and tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 85 publications
0
70
0
2
Order By: Relevance
“…It is, however, exceedingly difficult to establish the nature of the active species generated in situ, not least because low valent organometallic iron complexes are highly sensitive, often paramagnetic, and tend to "age" rapidly;moreover,the exact speciation is strongly dependento nt he chosen conditions and the presence/absence of polar additives in the mixture. [39] The mechanistic complexity of the current system is reflected in a number of control experiments, which showed that several well-defined but structurally quite distinct iron species are competent (pre)catalysts (see Table 1): thus, the intricate Fe(+ 2)-ate complex [(Me 4 Fe)·(MeLi)][Li·(OEt 2 )] 2 (entry 10), [33] two different Fe 0 olefin complexes (entries 14, 15), [37,40] and even catalytic amounts of Fe(CO) 5 (entry 11)o rt he derived pyridone complex (entry 12) workedw ell. In contrastt ot he oxophilicity of Fe(+ 2) and Fe(+ 3) salts, many low-valent iron species are inherently carbophilic;1,3-dienesa re amongst the privileged ligands which get activated towarda ttack by certain nucleophiles, for example, upon coordinationt ot he [Fe(CO) 3 ]f ragment.…”
Section: Resultsmentioning
confidence: 99%
“…It is, however, exceedingly difficult to establish the nature of the active species generated in situ, not least because low valent organometallic iron complexes are highly sensitive, often paramagnetic, and tend to "age" rapidly;moreover,the exact speciation is strongly dependento nt he chosen conditions and the presence/absence of polar additives in the mixture. [39] The mechanistic complexity of the current system is reflected in a number of control experiments, which showed that several well-defined but structurally quite distinct iron species are competent (pre)catalysts (see Table 1): thus, the intricate Fe(+ 2)-ate complex [(Me 4 Fe)·(MeLi)][Li·(OEt 2 )] 2 (entry 10), [33] two different Fe 0 olefin complexes (entries 14, 15), [37,40] and even catalytic amounts of Fe(CO) 5 (entry 11)o rt he derived pyridone complex (entry 12) workedw ell. In contrastt ot he oxophilicity of Fe(+ 2) and Fe(+ 3) salts, many low-valent iron species are inherently carbophilic;1,3-dienesa re amongst the privileged ligands which get activated towarda ttack by certain nucleophiles, for example, upon coordinationt ot he [Fe(CO) 3 ]f ragment.…”
Section: Resultsmentioning
confidence: 99%
“…Die Auswirkungen dieser bahnbrechenden Synthesen bis dato unbekannter metallorganischer Komplexe erstrecken sich auch auf die kritische Bewertung des Repertoires an Analysemethoden. Neidig und Mitarbeiter haben mit großer Sorgfalt aufgezeigt, dass paramagnetische, redoxaktive und/oder thermisch empfindliche Katalysatorzwischenstufen unter katalytischen Reaktionsbedingungen mithilfe von Operando‐Spektroskopien wie EPR, magnetischem Zirkulardichroismus und Mößbauer untersucht werden können (Schema ) …”
Section: Methodsunclassified
“…[1] Angewandte Chemie Sorgfalt aufgezeigt, dass paramagnetische,r edoxaktive und/ oder thermisch empfindliche Katalysatorzwischenstufen unter katalytischen Reaktionsbedingungen mithilfe von Operando-Spektroskopien wie EPR, magnetischem Zirkulardichroismus und Mçßbauer untersucht werden kçnnen (Schema 5). [19] Diese Untersuchungen metallkatalysierter Reaktionen haben auch die Mçglichkeit der Feinabstimmung von Katalysatoren über die Art des Gegenions aufgezeigt. Die cokatalytische Unterstützung durch Gegenionen kann verschiedene Arten der Substrat-oder Katalysatoraktivierung beinhalten.…”
unclassified
“…Multiple articles deal with the mechanism of Fecatalysed cross-coupling reactions and the oxidation state of the active species. [21] Thus, Fe(I), [18b,22] Fe (II), [19,23] or even Fe(-II) [18a,24] complexes have been proposed, detected or isolated. In the present case, the experimental evidence suggests the formation of radical iron species, which is compatible with an Fe(I/ III) catalytic cycle (Scheme 8).…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%